Эмануэль Гринберг - выдающиеся достижения в прикладной математике: радио-фильтры, корпуса танкеров, графы и интегральные схемы Emanuels Grinbergs - ievērojami sasniegumi lietišķajā matemātikā: radio filtri, kuģu korpusi, grafi un integrālās shēmas - Šneps-Šneppe, Manfrēds (International Journal of Open Information Technologies, 2018)
The paper is dedicated to the 50th anniversary of the Grinberg theorem. The main works of Emanuel Grinberg (1911-1982) in applied mathematics are described, following the stages of his life path, namely: the design of radio receivers and the calculation of radio filters (1949-1959), hull of tanker calculations (1962-1964), the study of graph theory and the proof of the Grinberg theorem (1968), designing of integrated circuits (1968-1980). Calculations of radio filters are associated with the expansion of the use of continued fractions for the analysis of linear electric circuits (the Kauer model) and the developing of new tools – the Grinberg brackets (as an extension of the Euler brackets), as well as the application of Chebyshev polynomials. Calculations of tanker hulls go back to the beginning of the theory of splines. The Grinberg theorem is a fundamental result of graph theory: it determines the necessary condition for a planar graph to contain the Hamiltonian cycle, that is, a closed path that passes through each vertex of a given graph exactly once. The Grinberg theorem is a generalization of Euler's problem (1736) about the seven bridges of Koenigsberg. The design of integrated circuits develops the Linvill model for semiconductors and the Ebers-Moll model for mathematical description of transistors and diodes. — Изложены основные работы Эмануэля Гринберга (1911–1982) по прикладной математике, следуя этапам его жизненного пути: проектирование радиоприёмников и расчеты радио-фильтров (1949-1959), расчеты обводов танкеров (1962-1964), занятия теорией графов и доказательство теоремы Гринберга (1968), проектирование интегральных схем (1968-1980) и получение Государственной премии Латвийской ССР в 1980 году. Расчеты радио-фильтров связаны с расширением применения цепных дробей для анализа линейных электрических схем (модель Кауера) и введением новых средств – расширенного произведения, что обобщает скобки Эйлера, а также применением полиномов Чебышева. Расчеты обводов танкеров восходят к началам теории сплайнов. Теорема Гринберга — это фундаментальный результат теории графов: определяет необходимое условие для планарного графа, чтобы граф содержал гамильтонов цикл, т.е. замкнутый путь, который проходит через каждую вершину данного графа ровно по одному разу. Теорема Гринберга является обобщением задачи Эйлера (1736) о семи мостах Кёнигсберга. Проектирование интегральных схем развивает модель Линвилла для полупроводников и модель Эберса-Молла для математического описания транзисторов и диодов.
Emanuel Grinberg - outstanding achievements in applied mathematics: radio filters, hulls of tankers, graphs and integrated circuits
Keywords: Emanuel Grinberg; radio-filter; continued fractions; Cauer model; Euler brackets; Chebyshev polynomials; tanker; theory of splines; graph theory; Grinberg theorem; integrated circuit; Linvill model; the Ebers-Moll model.